1992
DOI: 10.1017/s0950268800050500
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing oral carriage of yeasts among individuals with diabetes mellitus

Abstract: SUMMARYA total of 439 individuals with diabetes mellitus were examined for carriage of yeasts by the oral rinse and palatal swab techniques. Eighteen genetic or environment variables were assessed for their contribution to carriage of yeasts. The factor contributing to palatal and oral carriage of yeasts among individuals with insulin dependent diabetes mellitus (IDDM) was age (P < 0-01). The factor contributing to palatal carriage of yeasts among individuals with non-insulin dependent diabetes mellitus (NIDDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
4
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 19 publications
2
30
4
1
Order By: Relevance
“…Results from this study revealed that diabetes mellitus might enhance oral candidal colonization and proliferation (11,25). On the contrary, Pinducciu and colleagues (1997) did not notice any significant difference in the isolation of both anaerobic and aerobic microbial flora in 31 diabetics and 20 non-diabetics.…”
Section: Distribution Of Microbes With Respect To Oralcontrasting
confidence: 56%
“…Results from this study revealed that diabetes mellitus might enhance oral candidal colonization and proliferation (11,25). On the contrary, Pinducciu and colleagues (1997) did not notice any significant difference in the isolation of both anaerobic and aerobic microbial flora in 31 diabetics and 20 non-diabetics.…”
Section: Distribution Of Microbes With Respect To Oralcontrasting
confidence: 56%
“…Accurate identification of strains isolated from diabetic patients is especially important because they are more likely to carry species other than C. albicans which might not be sensitive to certain antifungal agents. 1,7 Recently, Goswami et al reported that C. glabrata (39%) was a predominant species isolated from vagina of diabetic Indian women and C. albicans was detected only in 26%. Surprisingly, in healthy women C. glabrata was as frequent as C. albicans (30%).…”
Section: Discussionmentioning
confidence: 99%
“…1 The influence of diabetes on the frequency of fungal invasion is still unclear. We did not find any published study considering glycemia in diabetic pregnancies and its relation to mycoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the reasons making diabetic patients more susceptible to oral candidiasis are high levels of salivary glucose, low secretion of saliva, impaired chemotaxis, and defect of phagocytosis due to polymorphonuclear leukocyte deficiency. The attachment of C. albicans to the crystalline hydroxyapatite produces collagenolytic enzyme, which increases crystal solubility and consumes nitrogen of dentin collagen in DM patients [8,9,10] .…”
Section: Introductionmentioning
confidence: 99%